Construction of the Evaluation Index System for the Sustainable Development of Primary School Campus Football in Shaanxi Province, China - Fan , XiaoYu; Sungkawadee, Panya (International Journal of Sociologies and Anthropologies Science Reviews, 2023)
Background and Aim: This study expounds the theoretical framework for constructing the evaluation index system for the sustainable development of elementary school football in Shaanxi Province, including the final evaluation index system and evaluation methods. The main objective of this research was to develop the evaluation index system for football in elementary schools in China’s Shaanxi province. Materials and Methods: The populations of this research include educational experts, physical education experts, teachers or university teachers, experts in the direction of football, campus football managers, and football coaches. Consult 5 experts through questionnaires and then using the Delphi method, the expert questionnaires were distributed to 19 experts, and two rounds of questionnaires were distributed and collected to screen out the core indicators and then determine the index weight of the sustainable development evaluation system of primary school football in Shaanxi Province, finally use the fuzzy comprehensive evaluation method to evaluate the sustainable development ability of Xi’an primary school football. Result: (1) Construct the sustainable development evaluation index system for primary school football in Shaanxi Province, including 4 first-level indicators, 13 second-level indicators, and 48 third-level indicators. (2) The first-level indicator, "organizational leadership and policy" is higher than the other three indicators, accounting for 31%. The second-level indicators, the weight of the four indicators of "implementation of national policies", "improvement of rules and regulations", "physical education hours", and "campus football culture" all exceed 10%, and there should be more support and supervision in the development process. Among the third-level indicators, the weight of the two indicators of "after-school training and competition rules and regulations" and "the number of football-themed campus cultural activities" exceeds 5%. The weight of the six indicators of "Rules and Regulations", "Number of Weeks", "Length of a Single Class", and "Extracurricular Activities" exceeds 3.5%. Conclusion: The research findings were: (1) There are 65 indicators of first-level, second-level, and third-level sustainable development of primary school campus football in Shaanxi Province, China. (2) Determine the weight ratio of indicators at all levels. (3) Through empirical research, the level of sustainable development ability of campus football in primary schools in Xi’an is obtained.